A pilot evaluation of group-based programming offered at a Canadian outpatient adult eating disorders clinic. (October 2016) - Mac Neil, Brad A.; Leung, Pauline; Nadkarni, Pallavi; Stubbs, Laura; Singh, Manya
Highlights: The results of this pilot study showed that group-based treatment programming for Canadian adults struggling with a DSM-5 diagnosis of an eating disorder were viewed as being fairly satisfying by patients completing the treatment. Overall, participation in the group programming was linked with increased satisfaction with life post-group treatment. Participation in group programming was associated with decreased depressive and psychological symptoms of an eating disorder. Program evaluation represents an important component of a comprehensive adult eating disorder program as it provides a window into patients experiences, their satisfaction with the types of treatment services received, and a measure of whether a program is providing services that are effective in symptom reduction. Abstract: Eating disorder clinics across Canada place heavy reliance on group-based programming. However, little work has examined whether this modality of treatment is well-received by patients and results in clinical improvements. The purpose of this pilot study was to evaluate patient satisfaction and outcomes for group-based programming offered through an adult eating disorders clinic. Participants were 81 adults who met DSM-5 criteria for an eating disorder and participated in the study as part of the clinic's program evaluation. Participants received medical monitoring, psychiatric follow-up, adjunct nutrition and pre-psychological treatment, and participated in the clinic's core cognitive behavioural therapy (CBT) group. Demographic information and weight were collected at intake. Participants also completed pre- and post-group programming measures of life satisfaction, depressive and anxiety symptoms, psychological symptoms of the eating disorder, and satisfaction with the programming. Participants' experienced a significant increase in satisfaction with life, and decreases in depressive symptoms and psychological symptoms of the eating disorder post-group. Adults endorsed feeling fairly satisfied with the group-based services provided. Results draw attention to the importance of program evaluation as an integral component of an adult outpatient eating disorder clinic by providing a voice for patients' views of the services received and program outcomes.